LEKSYKA TEKSTÓW AKTÓW PRAWNYCH - Redakcja (Wydział Prawa i Administracji UAM, 2006)
The paper is an attempt to find the place o f the lexis o f legal acts in the varieties of the Polish language lexis, and to verify the thesis claimed by lawyers that the vocabulary used in legal texts is colloquial. The study was carried out using linguistic research methods and lexicographic dictionaries of Polish language. The main conclusions that could be drawn were that the texts of legal acts are official, and the language used in them is not colloquial. The analysis of the legal texts has shown that the legal vocabulary consists of two layers: (i) one basic lexis, common to all Polish (neutral, standard) and (2) specific lexis, differentiating it from others, composed of: (a) legal words, as referred to in dictionaries o f Polish language, (b) legal words as defined in legal texts, legal science or jurisdiction, and as such part of the general legal vocabulary, and (c) vocabulary of the official variety of Polish language (reserved for books, official documents, professional and scientific texts). The language of legal texts is not a colloquial form which in itself is a variety of Polish language, but unofficial, met only in oral discourse. The language of legal texts is beyond any doubt only written, and the words and expressions contained in legal texts sre not described in dictionaries of Polish language as colloquial
LEXIS OF LEGAL ACTS